Investigation of Vortex Formation in Water Intake Structures by Computational Fluid Dynamics - Kaya, Nihat; Tunc, Mustafa; Evranos, Osman Bedreddin (Springer Int Publ Ag, 2022)
In this study, the vortex formed on the upstream of the frontal water intake structure in a dam lake was investigated by numerical modeling. Using the computational fluid dynamics method, vortex formation for different water levels was examined numerically. The purpose of this study is to prevent the formation of vortex, which can cause serious damage to the hydraulic structure. The water intake structure examined in the study has three units and rectangular shapes. The geometrical areas of each unit in the water intake structure are equal. The discharge and the distance between the side curtain walls were kept constant. The pressure at the inlet of the water intake structure has been changed depending on the height of the water level. The model scale of the water intake is 1/40. Froude model affinity was used as the model scale. In the numerical study, air intakes to the extent of serious damage to the structure and vortex formations have been observed. Visual simulations and analysis results of numerical models prepared and analyzed in FLOW-3D were examined in FlowSight. The first numerical models are based on examining the vortexes in the water intake structure, and the later numerical models are on the structures that prevent the vortexes in the water intake structure. Vortex formation in hydraulic structures is an undesirable physical phenomenon. Especially in dams with hydroelectric power plants, it causes serious damage to energy efficiency loss, water intake structure, shortening the service life of turbines and energy tunnels. Due to these problems, different anti-vortex structures were tested on the numerical model by CFD method in order to eliminate or reduce the negative forces from vortexes. Structures that block the tested vortex may allow to increase the operating water level in the dam reservoir. A new water intake structure model has been created for the solution of this hydraulic problem, which may cause great danger. Thanks to the new models created, it has been observed that air intake and vortex formations occur in a way that will cause less damage to the hydraulic structure in question.
Keywords: Water intake structure; Vortex formation; Anti-vortex structure; Computational fluid dynamics; FLOW-3D